1985
DOI: 10.1163/156853885x00362
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoiesis and Regeneration: Changes in the Liver, Spleen, Bone Marrow and Hepatic Iron Content during Tail Regeneration in the Scincid Lizard, Mabuya Carinata (Boulenger)

Abstract: In response to the observed changes in blood during tail regeneration, a detailed histophysiological study of the haemopoietic organs such as liver, spleen and bone marrow was undertaken. During regeneration, all three organs were found to undergo histophysiological changes. Increased haemopoietic activity in the marrow and hyperplasia of the white pulp were the important changes shown by the bone marrow and spleen respectively. In the liver, the most marked effect appeared to be the formation of large numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Together with the previous studies on the fluctuation of blood cell types during tail regeneration in lizards (Alibardi, ; Hiradhar et al, ; Ramachandran et al, ; Shah et al, ), this study has indicated that the bone marrow and blood vessels supply the granulation tissue of the preblastema with circulating and still maturing blood cells that are utilized for immunitary defence before mesenchymal cells replace these hematogenous cells in the growing blastema (Alibardi, ; Alibardi and Sala, ).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Together with the previous studies on the fluctuation of blood cell types during tail regeneration in lizards (Alibardi, ; Hiradhar et al, ; Ramachandran et al, ; Shah et al, ), this study has indicated that the bone marrow and blood vessels supply the granulation tissue of the preblastema with circulating and still maturing blood cells that are utilized for immunitary defence before mesenchymal cells replace these hematogenous cells in the growing blastema (Alibardi, ; Alibardi and Sala, ).…”
Section: Discussionsupporting
confidence: 73%
“…During tail regeneration, not only in the circulating blood and in the blastema but also in hemopoietic organs such as spleen and liver, there is a production of many blood cells (Ramachandran et al, ; Shah et al, ). In the liver, nodules of lymphocytes are generated (Ramachandran et al, ), and in the spleen, the white pulp increases (Shah et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations